Pengembangan Konsep Pariwisata untuk Memperkuat Fondasi Pelestarian Budaya dan Spiritual Bali - Budiasih, Ni Made (PARIWISATA BUDAYA: JURNAL ILMIAH AGAMA DAN BUDAYA, 2018)
Culture and life in Bali is very potential in bringing tourists to Bali, besides the natural beauty of Bali is also known for the culture and spiritual order is thick that does not exist in other parts of the world. In this discussion will develop the concept of tourism in Bali to be friendly and strengthen the foundation of preserving Balinese culture itself in the choice of travel options for tourists both local and international. This development focuses on engaging the tourists in the cultural process and life in Bali itself by keeping in mind its limitations. By making tourists familiar with Bali deeper is expected to bring added value that can develop cultural preservation by getting investment from tourists for the process of preservation of culture and the next generation began more interested in its own culture because it can bring a clear income that has been feared so many generations successors choose to become tourist service employees such as hotels, tours, and the like compared to a cultural activist who is actually more sought after by foreign tourists. Keyword: tourism, culture, spiritual, preservation, next generation, tourists